Design and protocol of a comprehensive multicentre biobank for abdominal aortic aneurysms - Jaap F Hamming; Hamid Jalalzadeh; Reza Indrakusuma; Jan D. Blankensteijn; Willem Wisselink; Kak K Yeung; Jan H N Lindeman; Mark J W Koelemay; Dink A Legemate; Ron Balm (BMJ Open)
Introduction The pathophysiology and natural course of abdominal aortic aneurysms (AAAs) are insufficiently understood. In order to improve our understanding, it is imperative to carry out longitudinal research that combines biomarkers with clinical and imaging data measured over multiple time points. Therefore, a multicentre biobank, databank and imagebank has been established in the Netherlands: the ‘Pearl Abdominal Aortic Aneurysm’ (AAA bank).Methods and analysis The AAA bank is a prospective multicentre observational biobank, databank and imagebank of patients with an AAA. It is embedded within the framework of the Parelsnoer Institute, which facilitates uniform biobanking in all university medical centres (UMCs) in the Netherlands. The AAA bank has been initiated by the two UMCs of Amsterdam UMC and by Leiden University Medical Center. Participants will be followed during AAA follow-up. Clinical data are collected every patient contact. Three types of biomaterials are collected at baseline and during follow-up: blood (including DNA and RNA), urine and AAA tissue if open surgical repair is performed. Imaging data that are obtained as part of clinical care are stored in the imagebank. All data and biomaterials are processed and stored in a standardised manner. AAA growth will be based on multiple measurements and will be analysed with a repeated measures analysis. Potential associations between AAA growth and risk factors that are also measured on multiple time points can be assessed with multivariable mixed-effects models, while potential associations between AAA rupture and risk factors can be tested with a conditional dynamic prediction model with landmarking or with joint models in which linear mixed-effects models are combined with Cox regression.Ethics and dissemination The AAA bank is approved by the Medical Ethics Board of the Amsterdam UMC (University of Amsterdam).Trial registration number NCT03320408.